Prevalence of impaired glucose tolerance test and diabetes in overweight, obese and apparently healthy school going adolescents - Choudhary, Kirti; Mathur, Priyanshu; Garg, Manisha; Gupta, P. P. (International Journal of Contemporary Pediatrics, 2017)
Background: Adolescence is a period of transition from childhood to adulthood. It occupies a crucial position in the life of human beings characterized by an exceptionally rapid rate of growth in physical, mental, sexual, and psychological behavior etc. The present study was planned to study the prevalence of impaired glucose tolerance amongst overweight, obese and apparently healthy school going adolescents in the city of Jaipur, Rajasthan. Methods: The study has been conducted in the Department of Pediatrics of Mahatma Gandhi Medical College of Mahatma Gandhi University of Medical Sciences and Technology, Jaipur. The study was a cross sectional analytical study conducted in schools of Jaipur. This study was done from August 2011 to November 2011 and 180 patients of aged between 10 to 18 years of age were enrolled. Results: In this study, it was found that the prevalence of overweight to be 32.65 percent in males and 34.15 percent in females. It was seen that 33.67 percent males and 32.93 percent females belonged to the obese category. Out of 180 adolescents, 25 (13.89 percent) were found to have IGT and only 1 was found to have type 2 diabetes (0.5 percent). Out of 25 students with IGT, 15 were boys and 10 were girls. Among these 25 students with IGT, 9 were overweight and 16 were obese. 15 percent of overweight student and approximately 26 percent of obese students had IGT. The association of IGT and increased BMI was found to be highly significant. Conclusions: The present study highlights the fact that type 2 diabetes in children occurs in developing counties and there is an increase need to look for type 2 diabetes in overweight and obese children and adolescents in India. Therefore, it is recommended that all obese and overweight adolescents should be screened at least yearly for type 2 diabetes mellitus using OGTT so that timely intervention can be done.